2015
DOI: 10.1504/lrj.2015.069803
|View full text |Cite
|
Sign up to set email alerts
|

When the original is beyond reach: consumer perception and demand for counterfeit luxury goods in Germany and South Korea

Abstract: Abstract:The tremendous growth in the luxury market in the last decades has been accompanied by a prevalence of pirated and counterfeit goods. Reasoning that all governmental efforts and management actions to curtail counterfeit activities will not be sufficient as long as counterfeiters face such an immense demand for their products, the importance of focusing on the consumer perspective becomes evident. In this context, the aim of this study is to provide and empirically investigate a comprehensive framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
1
18
0
3
Order By: Relevance
“…Counterfeiting refers to the unauthorized production of goods that are normally protected by trademarks, copyrights, or patents (Hennigs et al, 2015;Shultz & Saporito, 1996). Counterfeiting could be either deceptive or nondeceptive (Eisend et al, 2017;Randhawa, Calantone, & Voorhees, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Counterfeiting refers to the unauthorized production of goods that are normally protected by trademarks, copyrights, or patents (Hennigs et al, 2015;Shultz & Saporito, 1996). Counterfeiting could be either deceptive or nondeceptive (Eisend et al, 2017;Randhawa, Calantone, & Voorhees, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In recent years, there has been increased demand for counterfeit goods (Amaral & Loken, 2016;Teah, Phau, & Huang, 2015), suggesting that the efforts made by different governments and luxury brand manufacturers to curb counterfeit activities appear to be having minimal effect on consumers (Hennigs et al, 2015;Wilcox, Kim & Sen, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivation for exploring this topic and this specific problem arose from examining new trends in the luxury goods markets, which might even threaten traditional corporate strategies. An overview of relevant scientific and expert literature and other sources was conducted, and it was found that scholastic literature mainly focuses on assessing the psychological aspects of consumer's desires for luxury goods for displays of wealth, status and prestige (Han et al, 2010;Hennigs et al, 2015;Hennigs et al, 2016). Many different characteristics of luxury goods have been assessed (Kasztalska, 2017;Tekin et al, 2016;Fuerst and Shimizu, 2016;Hennigs et al, 2015;Hennigs et al, 2016), as well as luxury purchasing motivations (Han et al, 2010;Caserta, 2008;Yang and Mattila, 2017) and influencing factors on consumer buying behaviour of luxury goods (Nwankwo et al, 2014;Ramya and Mohamed, 2016;Singh et al, 2014;Tekin et al, 2016;Thangasamy and Patikar, 2014), all of which play a major part in affecting and forming consumer behaviour in buying luxury goods.…”
Section: Introductionmentioning
confidence: 99%
“…Since the issue had become crucial, the academic studies (Eisend & Schuchert-Guler, 2006;Albers-Miller, 1999;Wiedmann et al, 2007;Ang et al, 2001;Bloch et al, 1993;Fernandes, 2013;Tom et al, 1998;Gentry et al, 2006;Wee et al, 1995;Yoo & Lee, 2009;Penz & Stottinger, 2005;Engizek & Sekerkaya, 2015a;Hennigs et al, 2015) focused on the demand side of the counterfeiting of luxury brands.…”
mentioning
confidence: 99%